Optimizing Digital Marketing Strategy to Increase the Competitiveness of Local UMKM in the Digital Era - Sherla Dara Rizky; Eloh Bahiroh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This journal investigates efforts to optimize digital marketing strategies to increase the competitiveness of local Micro, Small and Medium Enterprises in the digital era. Technological developments and changes in consumer behavior have driven a significant shift in the way UMKM market their products and services. This research aims to identify the most effective and relevant digital marketing strategies for local UMKM, as well as analyze their impact on increasing their competitiveness in an increasingly competitive digital market. Experimental quantitative research methodology involving data analysis, surveys and case studies of a number of local UMKM that have implemented digital marketing strategies. The results of the research analysis show that the average difference in scores before and after the intervention in the intervention group was 15.07, with a t test statistical value of 11.16 and a significance level (p-value) very close to zero (p < 0.001), this shows that there is a significant influence use of media to increase UMKM marketing. The interviews also showed that the use of social media, content marketing, is a key factor in increasing the exposure of UMKM and their attractiveness to digital consumers. These findings can provide valuable guidance for local UMKM in facing digital challenges and improving their position in the rapidly developing digital era.